2015
DOI: 10.21273/hortsci.50.4.628
|View full text |Cite
|
Sign up to set email alerts
|

Soaking, Temperature, and Seed Placement Affect Seed Germination and Seedling Emergence of Litchi chinensis

Abstract: To find efficient ways to increase the percentage of seed germination and seedling emergence in litchi (Litchi chinensis Sonn.), we investigated the effects of soaking and high temperature on seed germination, as well as the influence of seed placement (orientation and burial depth) on seedling emergence. Seeds of most tested litchi cultivars soaked in water had a better germination performance than seeds without soaking. More than 90% germination of tested litchi seeds was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This implies that there is an intra-specific variation in germination response among Balanites aegyptiaca seeds. Variation in germination response of seeds of different species when placed in a different position during sowing is common (Elfeel, 2012;Kelvin et al, 2015;Zhang et al, 2015) but variation among similar species is not common. Variation in seed characteristics among Balanites aegyptiaca species has been reported by Aviara et al (2005).…”
Section: Germination Percentagementioning
confidence: 99%
See 2 more Smart Citations
“…This implies that there is an intra-specific variation in germination response among Balanites aegyptiaca seeds. Variation in germination response of seeds of different species when placed in a different position during sowing is common (Elfeel, 2012;Kelvin et al, 2015;Zhang et al, 2015) but variation among similar species is not common. Variation in seed characteristics among Balanites aegyptiaca species has been reported by Aviara et al (2005).…”
Section: Germination Percentagementioning
confidence: 99%
“…Seeds must be placed in a position that allowed the uptake of water and other environmental variables required for germination (Bowers and Hayden 1972). In some instances the effect of sowing orientation on seed germination was reported to be significant (Elfeel, 2012;Zhang et al, 2015) while in another instance it was reported to be non-significant (Kelvin et al, 2015). This implies that the seed of different species responds differently during germination to the position of sowing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the seeds sown germinated faster in Daloa and Montpellier because of the relatively high and humid temperatures and the richness of the soil. Indeed, while light allows plants to develop (elaboration of structure), heat favours growth (dry matter gain) and thus rapid seed dormancy [70] [71]. The minimum period between the first germination and the last germination was 16 days in Korhogo (seeder 1), 8 days (seeder 6) in Daloa and 7 days (seeder 3) in a controlled environment.…”
Section: Germination Parametersmentioning
confidence: 99%
“…Treatment of seeds priming by soaking seeds in water (hydropriming) and other chemical compounds (osmopriming) for a particular time potentially increases the ability of wild banana seeds to germinate. Seeds priming has been tested in several plants, such as lychees (Zhang et al, 2015), culantro Eryngium foetidum (Mozumder & Hossain, 2013), tomatoes (Sabongari & Aliero, 2004), and pistachios (Esmaeilpour & Van Damme, 2016). The success of seed priming in increasing germination is influenced by several factors such as the type of priming, concentration of the chemical compound, imbibition time, and the variety of species (Pawar & Laware, 2018).…”
Section: Introductionmentioning
confidence: 99%